2017
DOI: 10.4103/2249-4863.222016
|View full text |Cite
|
Sign up to set email alerts
|

Depression and its associated factors among people living with HIV/AIDS: Can it affect their quality of life?

Abstract: Introduction:Depression, being the most common neuropsychiatric complication of HIV, is also associated with increased health-care utilization, decreased quality of life (QOL), and poor adherence to antiretroviral therapy (ART). Depression is a multidimensional disorder affected by a variety of biological, psychological, and social determinants and this relation becomes more complicated in HIV patients. The current study therefore aimed to investigate the sociodemographic and clinical determinants of depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 13 publications
6
53
1
3
Order By: Relevance
“…Given the higher reported prevalence estimates of depression among females in the general population, females were considered to be more vulnerable than males to the onset of depression [ 122 ], a finding supported by evidence from studies conducted in PLHA populations. In a observational cross-sectional study conducted in central India recruiting a large sample of 1181 PLHA, Deshmukh et al have found that a greater percentage of females was screened positive for depressive symptoms when compared with males (59.9% vs 43.7%, p < 0.001) [ 123 ]. In another cross-sectional study conducted in Nigeria, a significantly higher prevalence of major depressive disorders was reported among females than among males [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the higher reported prevalence estimates of depression among females in the general population, females were considered to be more vulnerable than males to the onset of depression [ 122 ], a finding supported by evidence from studies conducted in PLHA populations. In a observational cross-sectional study conducted in central India recruiting a large sample of 1181 PLHA, Deshmukh et al have found that a greater percentage of females was screened positive for depressive symptoms when compared with males (59.9% vs 43.7%, p < 0.001) [ 123 ]. In another cross-sectional study conducted in Nigeria, a significantly higher prevalence of major depressive disorders was reported among females than among males [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study conducted in HIV-infected adults undergoing anti-retroviral treatment demonstrated that participants older than 50 years old had a two times higher risk of depression when compared with participants with between 18 and 30 years old [ 129 ]. In addition, the result from the study which used the Depression, Anxiety, Stress subscales, and full Scale (DASS-21) for depression screening showed that no significant effect of age on the rate of depression was found among PHLA [ 123 ]. In this meta-analysis, although no significant association was found between age and the pooled prevalence of depression, age was demonstrated to be linked with a higher risk of depression in studies with Zung SDS scores ≥50 or CES-D-20 scores ≥16 as the criteria for screening positive, which might support the positive association between age and depression among PLHA to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of persons living with HIV seen at the Almaty AIDS Center reported symptoms consistent with an acute depressive episode; no patient was treated for depression. The estimated prevalence falls in the middle of prevalences estimated by a WHO study of PLWHA that utilized clinical diagnostic interviews in five countries on four continents (range: 0% to 18.4% with an average of 7.1%), [ 12 , 14 ] and in the lower half of prevalence estimates when compared to studies of depression among PLWHA conducted worldwide (range 3% to 63%) [ 59 , 60 ]. The PHQ-9 tends to result in lower prevalence estimates [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 A study done at ART centre of tertiary care hospital found depression was significantly more prevalent in patients who belonged to lower socioeconomic class (50.7%) than those who belonged to middle and upper socioeconomic class (30.4%), in our study also socioeconomic status was significantly associated with depression (p=0.009), but PLHA belonging to middle class showed highest percentage of depression (43.5%) followed by 40.8% and 23.4% depression among PLHA belonging to lower middle and lower socioeconomic groups respectively, may because middle class PLHA were more worried about of societal reaction to their positive HIV status. 16 The study showed no significant association between depression and age, place of residence, education, and marital status of the respondents. Almost similar results have also been found by Khan et al and few other studies.…”
Section: Discussionmentioning
confidence: 74%
“…7 No statistical association was found between CD4 count and depression in the present study which was similar to findings of study at Jhansi and few other studies. 7,12,16 Proportion of Depression was 65.5% among PLHA with less than one year of illness compared to 28.6% among PLHA with 5 years of illness, which was statistically significant (p=0.001). Similarly duration of ART was statistically associated with depression, as 61.1% of PLHA on ART for less than 1 year had depression compared to 28.6% of depression among PLHA who were on treatment for more than 5 years, but in other studies duration of illness or duration of ART were not associated with depression.…”
Section: Discussionmentioning
confidence: 84%